Developing Electronic-Based Picture Storybooks to Enhance Student Learning Motivation - Galih Puji Mulyoto; Tsamrotu Imani Mufida; Debi Ayu Puspitasari (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The purpose of this development research is to (1) determine the design of the development of illustrated storybook media for Pancasila and Citizenship Education subjects to maximize learning motivation for students of class II MI Roudlatul Huda (2) determine the appropriateness of the media for illustrated storybooks for Pancasila and Citizenship Education subjects. in order to maximize learning motivation for students of class II MI Roudlatul Huda (3) to determine the effectiveness of picture storybook media for Pancasila and Citizenship Education subjects in order to maximize learning motivation for students of class II MI Roudlatul Huda. The development and research of this method use the type of researching your research development (RnD). The development procedure uses the ADDIE model with five stages, namely (1) the analysis phase, (2) the design phase, (3) the development phase, (4) the implementation phase, (5) the improvement phase. This research was conducted at MI Roudlatul Huda Bibrik, Jiwan District, Madiun Regency. This data collection technique uses interviews and questionnaires. Data analysis using quantitative and qualitative data. The results of the development were carried out by researchers in the form of printed media learning media, namely the Picture Story Book media for Pancasila and Citizenship Education lessons, my daily task material. The results of research and development meet the criteria of validity, material experts get 73% and media experts get 85%. The results of the trial on MI Roudlatul Huda class II students to assess the attractiveness of the Picture Story Book by 97%. The results of students' learning motivation obtained an average score of 81 for the control class and 87 for the experimental class. Therefore, the development of picture storybook media is appropriate for students.